MECHANISMS OF OPERATIONAL PORTFOLIO MANAGEMENT OF PROJECTS IN SHIPBUILDING AND SHIP REPAIR - Nikolai Fateev; Iryna Zaporozhets (Economics & Education, 2021)
Over the past decades, the competitiveness of enterprises in the world shipbuilding and ship repair markets is being determined by the level of development of information and communication technologies, on the basis of which global value chains are being formed. The shipbuilding 4.0 methodology is being introduced in the industry, which is based on the advanced technologies of the fourth industrial revolution. The aim of the article is to study the models and mechanisms for portfolio management of shipbuilding and ship repair enterprises on the basis of modern information technology for the effective implementation of strategic goals and sustainable development. The basis of the organizational and methodological support of portfolio management of shipbuilding enterprises is a system of planning and accounting units. This is a three-level model for the shipbuilding work breakdown. The first level of work breakdown consists of shop stages (list of works performed by a certain production department). The second level of work breakdown is technological sets that are being formed in the process of production planning on the principles of structural and technological unity of work and are the basic elements in the intershop operational management. Technological operations are carried out at the third level of work breakdown (brigade sets). At the upper levels of shipbuilding work breakdown, all the key features of project management take place. Technological sets are recommended to be used as an information and analytical basis when developing the network models at the upper levels of structural work breakdown. The methodology for portfolio management of projects of a shipbuilding enterprise described in the article is aimed at aligning the goals and objectives of individual projects and the portfolio as a whole with the strategic plans of the enterprise.